Pressure and specific energy requirements for densification of compost derived from swine solid fraction - Pampuro, N.; Facello, A.; Cavallo, E. (Spanish Journal of Agricultural Research, 2013)
Compost derived from swine solid fraction is a low density material (bulk density less than 500 kg m-3). This makes it costly to transport from production sites to areas where it could be effectively utilized for value-added applications such as in soil fertilization. Densification is one possible way to enhance the storage and transportation of the compost. This study therefore investigates the effect of pressure (20-110 MPa) and pressure application time (5-120 s) on the compaction characteristics of compost derived from swine solid fraction. Two different types of material have been used: composted swine solid fraction derived from mechanical separation and compost obtained by mixing the first material with wood chips. Results obtained showed that both the pressure applied and the pressure application time significantly affect the density of the compacted samples; while the specific compression energy is significantly affected only by the pressure. Best predictor equations were developed to predict compact density and the specific compression energy required by the densification process. The specific compression energy values based on the results from this study (6-32 kJ kg-1) were significantly lower than the specific energy required to manufacture pellets from biomass feedstock (typically 19-90 kJ kg-1).